Dragomelj – an Urnfield period settlement as part of the Podgorica-Dragomelj twin settlement and remains from the Early Iron Age - Peter Turk; Vesna Svetličič (Arheološki Vestnik, 2025)
The article presents the results of the investigations at Dragomelj, where habitation remains from the Urnfield period represent the northern part of a twin settlement together with the southern part at Podgorica. The unearthed residential and other buildings were poorly preserved, but did reveal numerous spinning and weaving implements, as well as a variety of pottery. Together with radiocarbon dates, they place the settlement in the Rogoza–Orehova vas horizon of the 12th and 11th centuries BC. They also show that its inhabitants engaged in spinning and weaving activities, as well as storing a hoard of copper and bronze semi-products (Dragomelj I hoard) as a complement to the metallurgy and production-oriented part at Podgorica, south of the Pšata stream.